Lactobacillus plantarum and Lactobacillus reuteri as Functional Feed Additives to Prevent Diarrhoea in Weaned Piglets - Matteo Dell’Anno; Maria Luisa Callegari; Serena Reggi; Valentina Caprarulo; Carlotta Giromini; Ambra Spalletta; Simona Coranelli; Carlo Angelo Sgoifo Rossi; Luciana Rossi (Animals, 2021)
The effects of Lactobacillus plantarum and Lactobacillus reuteri and their combination were assessed in weaned piglets. Three hundred and fifty weaned piglets (Landrace × Large White), balanced in terms of weight and sex, were randomly allotted to four experimental groups (25 pens, 14 piglets/pen). Piglets were fed a basal control diet (CTRL, six pens) and a treatment diet supplemented with 2 × 108 CFU/g of L. plantarum (PLA, 6 pens), 2 × 108 CFU/g L. reuteri (REU, six pens) and the combination of both bacterial strains (1 × 108 CFU/g of L. plantarum combined with 1 × 108 CFU/g of L. reuteri, P+R, 7 pens) for 28 days. Body weight and feed intake were recorded weekly. Diarrhoea occurrence was assessed weekly by the faecal score (0–3; considering diarrhoea ≥ 2). At 0 and 28 days, faecal samples were obtained from four piglets per pen for microbiological analyses and serum samples were collected from two piglets per pen for serum metabolic profiling. Treatments significantly reduced diarrhoea occurrence and decreased the average faecal score (0.94 ± 0.08 CTRL, 0.31 ± 0.08 PLA, 0.45 ± 0.08 REU, 0.27 ± 0.08 P+R; p < 0.05). The PLA group registered the lowest number of diarrhoea cases compared to other groups (20 cases CTRL, 5 cases PLA, 8 cases REU, 10 cases P+R; p < 0.01). After 28 days, the globulin serum level increased in PLA compared to the other groups (24.91 ± 1.09 g/L CTRL, 28.89 ± 1.03 g/L PLA, 25.91 ± 1.03 g/L REU, 25.31 ± 1.03 g/L P+R; p < 0.05). L. plantarum and L. reuteri could thus be considered as interesting functional additives to prevent diarrhoea occurrence in weaned piglets.